PIDANA KERJA SOSIAL SEBAGAI INSTRUMEN HUKUM PIDANA UNTUK MENGURANGI BEBAN LEMBAGA PEMASYARAKATAN - Johnson Sahat Maruli Tua Pangaribuan (GEVANGENEN Jurnal Pemasyarakatan, 2025)
Correctional Institutions in Indonesia’s criminal justice system hold a fundamental role not only as facilities for serving prison sentences but also as centers for inmate rehabilitation based on the values of Pancasila. However, in practice, various issues persist, such as the deprivation of inmates’ rights, human rights violations, and overcapacity, all of which hinder the realization of correctional objectives. Therefore, more adaptive and humanistic legal breakthroughs are needed. The development of criminal law through the concepts of restorative justice and community service punishment reflects a paradigm shift from a retributive orientation toward rehabilitation and social reintegration. Restorative justice focuses on restoring relationships among offenders, victims, and society, while community service punishment offers an alternative form of sentencing that emphasizes tangible contributions to society and reduces the burden on correctional facilities. The inclusion of community service punishment in Law No. 1 of 2023 concerning the Criminal Code represents a progressive step in addressing the challenge of mass incarceration while promoting a more humane form of justice. Thus, community service punishment can be viewed as a tangible implementation of Satjipto Rahardjo’s theory of progressive law, which asserts that law must serve humanity, not the other way around.